Reductions in payments to the State Fund for the Rehabilitation of Persons with Disabilities (PFRON) as a tool to reduce non-wage labour costs in enterprises - Koza, Andrzej; Politaj, Adriana (Publishing House of Wroclaw University of Economics and Business, 2024)
In this study, the authors attempted to identify employment costs, with particular emphasis on non-wage employment costs in terms of payments to the State Fund for the Rehabilitation of Persons with Disabilities (PFRON) and the possibility of their reduction. The main purpose was to identify and verify the effectiveness of legal and financial solutions aimed at stimulating Polish enterprises to employ workers with reduced competitiveness on the labour market and constituting a form of compensation for their employment in the context of reducing non-wage labour costs. The following research hypothesis was formulated: applying financial penalties for not employing persons with disabilities is not severe enough for enterprises to significantly change their attitude towards employing such persons, even in the context of their systematically growing number, because the multidimensional costs of employing persons with disabilities are more severe than the penalties paid for not employing them. The conducted research and literature review allowed for identifying the basic factors and correlations between the severity of penalties and the employment level of persons with disabilities. A strong positive correlation was observed between their employment rate and the increase in the basis for imposing penalties. Employers, having noticed the increasing amounts of penalties, tried at least not to increase the basis for their calculation and systematically aimed at supplementing employment or obtaining reductions in payments as a result of a lower ratio or the amount of payments made to the Fund owing to the cooperation with the employers of people with disabilities authorised to provide them. The research covered the years from 2018 to 2022, the subjective scope included enterprises with at least 25 full-time employees and subject to the obligation of employing persons with disabilities. The following research methods were used: critical analysis of source literature and legal acts, descriptive method, statistical analysis and correlation analysis based on the Pearson correlation coefficient.
Argumenta Oeconomica, 2024, Nr 1 (52), s. 207-220
Keywords: employment costs; payments to the State Fund for the Rehabilitation of Persons with Disabilities; PFRON; employment determinants